2017
DOI: 10.3390/ijerph14050504
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Environmental Tobacco Smoke Exposure and Cardiovascular Disease and the Potential Modifying Effect of Diet in a Prospective Cohort among American Indians: The Strong Heart Study

Abstract: American Indians experience high rates of cardiovascular diseases (CVD). Environmental tobacco smoke (ETS) has been linked to CVD, possibly due to pro-inflammatory and oxidative stress pathways. We examined the relationship between self-reported exposure to ETS and fatal and nonfatal CVD incidence using Cox proportional hazards models among 1843 non-smoking American Indians participating in the Strong Heart Study. We also evaluated potential modifying effects of several dietary nutrients high in anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, smoking is well known as a risk factor for cardiovascular disease, and results from a strong heart-based study exploring the potential moderating effects of several dietary nutrients with high antioxidant activity on cardiovascular disease in relation to exposure to environmental tobacco smoke showed that participants exposed to environmental tobacco smoke had a higher risk of cardiovascular disease compared with those not exposed, and a greater risk of cardiovascular disease compared with those who had higher vitamin E intake, as well as a greater risk of cardiovascular disease compared with those who had higher vitamin E intake, as well as a greater risk of cardiovascular disease compared with those who had higher vitamin E intake. The effects of environmental tobacco smoke on cardiovascular disease incidence were greater in those with low vitamin E intake compared to those with high vitamin E intake ( 47 ). Of note, the three study centers in the Strong Heart Study reported different smoking prevalence rates and used self-reported exposure to environmental tobacco smoke, making it difficult to differentiate between smoking, secondhand smoke, and thirdhand smoke, which limits the generalization of the results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, smoking is well known as a risk factor for cardiovascular disease, and results from a strong heart-based study exploring the potential moderating effects of several dietary nutrients with high antioxidant activity on cardiovascular disease in relation to exposure to environmental tobacco smoke showed that participants exposed to environmental tobacco smoke had a higher risk of cardiovascular disease compared with those not exposed, and a greater risk of cardiovascular disease compared with those who had higher vitamin E intake, as well as a greater risk of cardiovascular disease compared with those who had higher vitamin E intake, as well as a greater risk of cardiovascular disease compared with those who had higher vitamin E intake. The effects of environmental tobacco smoke on cardiovascular disease incidence were greater in those with low vitamin E intake compared to those with high vitamin E intake ( 47 ). Of note, the three study centers in the Strong Heart Study reported different smoking prevalence rates and used self-reported exposure to environmental tobacco smoke, making it difficult to differentiate between smoking, secondhand smoke, and thirdhand smoke, which limits the generalization of the results.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,29,30 Notably, a recent study reported that diets low in vitamin E may increase the harmful effects of tobacco smoke on cardiovascular disease. 31 In our study, vitamin E intake was the only nutrient that demonstrated a change over time, with intakes at six months being significantly higher than intakes 3 months. The epidemiologic evidence relating fruit and vegetable intake to a reduction in CAD may be explained, at least in part, by the antioxidant content of these foods and the role of these antioxidants in preventing oxidative changes to low-density lipoproteins (LDL).…”
Section: Discussionmentioning
confidence: 44%
“…However, the risk of heart disease is still higher in this group compared to nonsmokers who also follow a heart-healthy diet (3). Rajkumar et al discovered that second-hand smokers who consume more vitamin have a reduced risk of developing CVDs compared to those who consume less E (39). While some studies have highlighted the crucial function of nutrition in maintaining good health, they suggest that diet not impact the relationship between smoking and disease.…”
Section: Discussionmentioning
confidence: 99%